2014
DOI: 10.31018/jans.v6i2.495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilizer levels on nutrient availability and yield of cotton on Vertisol at Rahuri, District Ahemadnagar, India

Abstract: The field experiment on effect of fertilizer levels on nutrient availability and yield of cotton on Vertisol was conducted at Mahatma Phule Krishi Vidyapeeth, Rahuri during May to September, 2008. The experiment was laid out in factorial randomized block design with three replications and two main treatments i.e. hybrid Bt RCH-2 and Non-Bt RCH-2 and nine sub treatments with different fertilizer doses i.e. F 1 -No recommended doses of fertilizer (RDF), F 2 -50 % RDF, F 3 -75 % RDF, F 4 -100 % RDF, F 5 -125 % RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…However, the differences between increamental level of RDF from 100 to 125 and from 125 to 150 % were not found to be significant as also reported by Deshpande et al (2014) andRawal et al (2015). Cotton, being an inderminate crop, the positive effect of applied fertilizers can be realized to the level to have the synchronized growth of vegetative and reproductive parts.…”
Section: Yieldsupporting
confidence: 58%
“…However, the differences between increamental level of RDF from 100 to 125 and from 125 to 150 % were not found to be significant as also reported by Deshpande et al (2014) andRawal et al (2015). Cotton, being an inderminate crop, the positive effect of applied fertilizers can be realized to the level to have the synchronized growth of vegetative and reproductive parts.…”
Section: Yieldsupporting
confidence: 58%
“…Crop growth, nitrogen and potassium uptake, total chlorophyll content, and dry matter yield of cotton plant are significantly enhanced by phosphorous [69]. The application of phosphorous leads to increased phosphorous uptake and content in leaf, stem, and reproductive parts such as seeds [70]. Phosphorous has a stimulating effect on number of flower buds and bolls per plant as well as is essential for cell division.…”
Section: Phosphorusmentioning
confidence: 99%
“…Field experiments were conducted for three years during Kharif, 2009-2011 to study the effect of foliar application of nutrients (N, Mg, Fe, Zn, Mn and B) on growth and yield parameters of Bt cotton and results of pooled data indicated highest seed cotton yield with application of MgSO 4 1.0%+ ZnSO 4 0.5% (Singh et al, 2015). The field experiment on effect of fertilizer levels on nutrient availability and yield of cotton on Vertisol was conducted at Rahuri and found that the application of 100% RDF+1% MgSO 4 sprays recorded highest yield of Bt and non-Bt cotton hybrids (Deshpande et al, 2014). Shivamurthy and Biradar (2014) conducted an experiment at Dharwad in medium black soils and revealed that application of 1% solution of 19:19:19 water soluble fertilizers at 70, 90 and 110 DAS along with RDF+FYM+3 foliar sprays of 1% MgSO 4 +soil application of MgSO 4 @ 25 kg ha -1 recorded significantly higher number of bolls plant -1 and boll weight over RDF+FYM+ water spray.…”
Section: Effect Of Secondary and Micro Nutrients On Yield And Yield Amentioning
confidence: 99%